PENGARUH KESADARAN WAJIB PAJAK, SANKSI PAJAK DAN PROGRAM SAMSAT J’BRET TERHADAP KEPATUHAN WAJIB PAJAK PADA KANTOR SAMSAT KOTA BOGOR - Muhlis Muhlis; Benny Osta Nababan; Zeze Zakaria Hamzah; Kitty Emma Wandasari (Economicus : Jurnal Ekonomi dan Manajemen, 2023)
This study was conducted to determine the effect of Taxpayer Awareness, Tax Sanctions and the SAMSAT J'bret Program partially or simultaneously on Taxpayer Compliance at the SAMSAT Office in Bogor City. The variables in this study consist of independent variables, namely Taxpayer Awareness, Tax Sanctions and the SAMSAT J'bret Program while the dependent variable is Taxpayer Compliance. This type of research is quantitative. The research was conducted directly at the SAMSAT Bogor City Office located Jl. Ir. H. Juanda No. 4, Pabaton Neighborhoods Central Bogor District, Bogor City, West Java, 16121. The sample in this study is 100 taxpayers who pay motor vehicle tax at the SAMSAT Office in Bogor City. Data collection techniques using questionnaires. As for data analysis using Validity Test, Reliability Test, Classical Assumption Test, Multiple Regression Analysis Test and Hypothesis Test. The results of the study showed that partially and simultaneously the variables of Taxpayer Awareness, Tax Sanctions and the SAMSAT J'bret Program affect Taxpayer Compliance at the SAMSAT Office in Bogor City. The variables of Taxpayer Awareness, Tax Sanctions and the SAMSAT J'bret Program can only explain the variable of Taxpayer Compliance by 22%.